Extracellular vesicles derived from inflamed murine colorectal tissue induce fibroblast proliferation via epidermal growth factor receptor. (15th September 2020) - Hasegawa, Kana; Kuwata, Keiko; Yoshitake, Jun; Shimomura, Sayako; Uchida, Koji; Shibata, Takahiro
Abstract : Inflammatory bowel diseases (IBDs), such as Crohn's disease and ulcerative colitis, are chronic inflammatory disorders of the gastrointestinal tract. Although IBDs increase the risk of colitis‐associated colon cancer, the underlying mechanisms are not fully understood. Extracellular vesicles (EVs) are lipid‐bound sacs that transport proteins, RNA, and lipids between cells and are key mediators of cellular communication in both physiological and pathological settings. EVs have been implicated in many cancer hallmarks, including uncontrolled tumor growth and metastasis. In this study, we investigated the effects of colon‐derived EVs on the proliferation of fibroblasts. We used comparative proteomics to characterize protein profiles of colorectal EVs isolated from healthy mice (Con‐EVs) and those with dextran sulfate sodium‐induced colitis (IBD‐EVs). The results showed that 109 proteins were upregulated in IBD‐EVs. Notably, expression of epidermal growth factor receptor (EGFR), which plays important roles in cell proliferation and development, was increased in IBD‐EVs. We then examined the effect of EVs on murine NIH3T3 fibroblasts and found that IBD‐EVs significantly promoted cell proliferation in EGFR‐ and ERK‐dependent manner. Our findings suggest that inflamed colon‐derived EVs promote tumor development thorough activation of fibroblasts. Abstract : We demonstrated that extracellular vesicles (EVs) secreted by murine colorectal tissue are internalized by fibroblasts. EVs derived from colitis model mice increased EGFR expression in NIH3T3 cells and promoted their proliferation through activation of the EGFR‐ERK signaling pathway. Our study offers new insights into the EV‐mediated pathogenesis of inflammatory bowel disease‐associated colorectal cancer, which may be helpful in developing new therapeutic strategies for inflammation‐associated tumors.